Application of a Water Pump Semi-Automation Controller to the Irrigation System for Rainfed Rice Fields in Wonorejo Village, Sragen - Rohmah, Ratnasari Nur; Supardi, Agus; Supriyono, Heru; Handaga, Bana; Mulyaningtyas, Akida (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Rice fields in Wonorejo Village are rainfed rice fields where farmers rely on rainwater to grow crops. To solve this problem, some farmers drill well on their farms, and use submersible water pumps to lift up water to distributed to the rice fields. Prior to this community service activity, the operation of the submersible pump was manually controlled. This operation method had a drawback where excessive irrigation often occurred that could result on damage agricultural commodities, energy waste, and inefficient working time. This community service offers a solution by providing semi-automatic switching devices that will help to overcome this problem. The installed devices replace simple manual switching tools, in which some are in already less safety condition. The device is equipped with a timer that can be used to control the pump automatically as desired, an overload protection component, and equipped with indicator lights that indicate three conditions: the pump is on, the pump is off, and the occurrence of disturbances in pump operation. Evaluation on this community service activities evaluation shows all partners involved in this activity, appreciate this activity, and wanted to be continued in the future.